The influence of cardiovascular fitness and ventilatory efficiency on fMRI assessed cerebrovascular reactivity in older adults - Novak, Tom S.; Mammino, Kevin; Bello, Medina; Paredes Spir, Isabella; Vernon, Mark; Krishnamurthy, Venkatagiri; Nocera, Joe R. (Frontiers in Physiology, 2025)
PurposeBiological aging has a profound impact on cerebral health. A prevalent factor thought to underpin overall brain health is healthy cerebrovascular function. Recent research suggests a beneficial relationship between cerebrovascular health and physical activity. Specifically, transcranial doppler (TDS) studies have shown that higher hypercapnic cerebrovascular reactivity (CVR) at the major cerebral arteries is associated with better cardiovascular fitness in older adults. Building on this previous literature, we tested the hypothesis that fMRI-based capillary/venous CVR dynamics would also demonstrate a positive relationship with cardiovascular fitness. We also explored whether the magnitude and direction of CVR-fitness relations are consistent across the whole brain or demonstrate regional heterogeneity.MethodsTwenty-one cognitively intact, older adults aged 65–80 years completed an fMRI-BOLD CVR scan in which individuals alternated between breathing normal room air and a hypercapnic gas mixture (5% CO2, 21% O2, balanced N2). Cortical atlas segmentation and voxel-wise CVR analyses were performed to explore regional specificity of CVR-fitness relations. To quantify cardiovascular fitness, participants were assessed with graded exercise testing where estimated VO2 max, VE/VO2 slope, and VE/VCO2 slope (ventilatory efficiency) outcomes were collected.ResultsIn contrast to the TDS literature, our multiple regression analysis found that higher estimated VO2 max, and greater ventilatory efficiency (lower VE/VCO2 slope) were associated with lower hypercapnic CVR (all p < 0.03). This inverse relation was consistent across all cortical ROI’s, however, estimated VO2 max outcomes accounted for considerably more variance in CVR at the frontal, temporal, and parietal ROI’s, while greater ventilatory efficiency (VE/VCO2) exhibited a strong relation with lower CVR across the cortex.ConclusionThis work suggests that cardiovascular fitness is associated with cortical CVR, however, the strength and direction of this relationship may depend largely on the vascular beds being measured. Considering the complex array of physiological mechanisms contributing to BOLD-CVR (I.e., endothelial, glial, mitochondrial function) future studies using multi-modal CVR assessment can further inform the specificity of neural and vascular-based CVR adaptations in the aging brain.